"I Preferred to Take Another Activity From the Textbook": An Activity–Theoretical Study of Learning to Design Language Teaching Materials. Issue 4 (8th November 2022) - Carabantes, Luis; Paran, Amos
Abstract: Using activity theory, an offshoot of sociocultural theory, we examined how a group of preservice teachers (PSTs) of English in Chile learnt to design language teaching materials. Data from PSTs, teacher educators, and mentoring teachers shows how the conceptual tool of "teaching English as teaching the textbook" is appropriated by a group of PSTs and how their development of teacher agency is undermined by textbooks during their practicum—as well as showing the influential role of mentoring teachers and teacher educators in the appropriation of this conceptual tool. The study discusses the implications of how textbooks are used for English‐as‐a‐foreign‐language teacher education. Abstract : Graphical abstract: